HUBUNGAN PERSEPSI GURU TENTANG GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DENGAN KINERJA GURU TK SE KECAMATAN AMPEK ANGKEK KABUPATEN AGAM PROVINSI SUMATERA BARAT - Pratiwi, Rahmi Yulisha; ', Zulkifli N; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to know whether there is correlation teacher’s perceptions of transformational leadership style principal and performance of kindergarten teacher of Ampek Angkek District of Agam West Sumatera Province. The population of this research is a kindergarten’s teacher of Ampek Angkek District of Agam West Sumatra as many as 94 teachers, of this research sample as many as 48 teachers were taken using Taro Yamane formula. The method used is Pearson Product Moment to see the relationship variables on teacher’s perceptions of transformational leadership style with the school head teacher performance. The technique of collecting data used questioner in Likert scale form. The technique of analyzing data used test and statistic analytical by using SPSS program for windows Ver.23. Based on the results obtained by testing the hypothesis that there is a significant positive relationship and teachers perceptions of transformational leadership style and performance of kindergarten teacher of Ampek Angkek District of Agam West Sumatera Province. It can be seen from the value of the correlation coefficient of rxy = 0.318 and 0.028 significance level of <0.05. The level of teachers 'perceptions about the relationship of transformational leadership style of principals with teacher performance are included in the low category with determinant coefficient in the amount 10,11%, meaning that teachers' perceptions of transformational leadership style of the principal influences on teacher performance as much as 10,11% .